Introducing point-of-care ultrasound through competency-based simulation education using a fractured chicken bone model - Nathan L Haas; Elise Hart; Mary RC Haas; Trent Reed (eScholarship Publishing, University of California, 2017)
Audience: Medical students and interns. Introduction: Integration of point-of-care ultrasound (PoCUS) into undergraduate medical education has many potential benefits, including reinforcing core anatomic and physiologic concepts, demonstrating clinical correlates to pathology, and aiding in learning of the physical examination. Patients, standardized patients, commercial training models, or cadavers are typically required for training students on PoCUS, and are associated with substantial costs to educators and medical schools. Objectives: To introduce medical students to PoCUS with an inexpensive, reproducible, and educationally effective model using fractured chicken bones set in gelatin, and to assess medical students' abilities to identify simulated long-bone fractures using PoCUS. Methods: Medical students are pre-tested with an affective style questionnaire, a multiple-choice knowledge test, and a hands-on skill test pertaining to PoCUS and assessment of long-bone fractures. The hands-on skill test consists of PoCUS evaluation of 16 chicken tibias (half of which are fractured) set in an opaque gelatin solution. Subjects undergo a standardized educational intervention consisting of a video and deliberate practice on clear gelatin models until a predetermined performance standard is met. The investigators defined the performance standard as successful identification of the presence or absence of fracture in five consecutive clear gelatin modules using correct technique. Subjects are post-tested using an affective style questionnaire, a multiple-choice knowledge test, and a hands-on skill test, and these are repeated eight weeks later to assess retention.